The correlation between ambulatory blood pressure parameters and cardiovascular risk factors in older adults with high-risk hypertension - Tran, Van Nam; Hoang, Huy Truong; Le, Thi Bich Thuan (Tạp chí Y Dược Huế, 2023)
Objective: To explore the correlation of 24-hour ambulatory blood pressure (BP) monitoring (ABPM) parameters and cardiovascular risk factors in older adults with high-risk hypertension. Material and method: A cross-sectional study was conducted on 96 older adults (≥ 60 years old) with treated high-risk hypertension. Socio-demographic and cardiovascular risk information were gathered. The patients were performed 24-hour ABPM. Results: The mean age was 70.88 ± 7.86 years, and 64.6% were women. The prevalence of cardiovascular risk factors was as follows: dyslipidemia: 80.2%, family history of hypertension: 54.2%, diabetes mellitus: 51%, smoking: 24%, prior stroke: 11.5%. Significant differences in 24-hour, awake, and sleep systolic BP were observed between men and women. There were significant correlations between 24-hour mean systolic BP with age (r = 0.229, p = 0.025), dyslipidemia (r = 0.223, p = 0.029), family history of hypertension (r = 0.214, p = 0.036), BMI (r = 0.212, p = 0.039), waist circumference (r = 0.226, p = 0.027) and creatinine level (r = 0.207, p = 0.043). There were significant correlations between 24-hour mean diastolic BP with BMI (r = 0.289, p = 0.004) and prior stroke (r = -0.224, p = 0.029). There were significant correlations between 24-hour mean BP with BMI (r = 0.268, p = 0.009), waist circumference (r = 0.220, p = 0.032) and prior stroke (r = -0.215, p = 0.036). Conclusion: There were significant correlations between ABPM parameters and cardiovascular risk factors in older adults with high-risk hypertension.